DAMPAK PERUBAHAN IKLIM TERHADAP MIGRASI LINGKUNGAN DAN KEAMANAN MANUSIA DI BANGLADESH - Madyar Dewi, Untari Narulita; Haqqi, Halifa; Mercia Karina (Indonesian Journal of International Relations, 2023)
The research explains the impact of climate change which resulted in environmental migration from Bangladesh to India. This study aims to analyze the impact of climate change on environmental migration from Bangladesh to India. The method used is a qualitative method with data collection through literature studies with the concept of human security by UNDP and the theory of environmental migration by Graeme Hugo. The results of this study indicate that the impact of climate change which is massively occurring in Bangladesh raises "push" and "pull" factors which result in environmental migration from Bangladesh to India. However, there are obstacles in the form of the entry of Bangladeshi people into India illegally and the implementation of policies that have limited information. This research can be used as a reference for further research.